Respostas fisiológicas de plantas jovens de Eucalyptus urophylla tratadas com bioestimulante sob deficit hídrico - Santos, Rayka Kristian Alves; Cairo, Paulo Araquém Ramos; Barbosa, Romário Pereira; Lacerda, Janderson de Jesus; Mafra Neto, Caio da Silva; Macedo, Theilon Henrique de Jesus (Ciência Florestal, 2019)
Biostimulants consist of a mixture of growth regulators that, when they are sprayed on plants, act on hormonal balance, enhancing its development. Stimulate® is a biostimulant composed by indole butyric acid (0.005%), kinetin (0.009%) and gibberellic acid (0.005%) which promotes root growth, improves water and nutrients uptake, and helps restore plant hormonal balance. This research was based on the hypothesis that Stimulate® spraying can be an alternate way to mitigate negative effects of soil water-limiting on plant growth. The experimental work was performed in greenhouse and aimed to evaluate physiological responses of young plants of Eucalyptus urophylla sprayed with different Stimulate® concentrations and submitted to the following irrigation regimes: full, partial and no irrigation. Leaf water potential, relative water content, net photosynthesis, plant height and main root length were measured. Under water-limited conditions, plants sprayed with Stimulate® showed higher net photosynthesis and relative water content had a less decrease, due to osmotic adjustment. Spraying with Stimulate® also provided greater plant height and longer main root length in plants under water deficit. We conclude that the use of Stimulate® can be a viable option to mitigate negative water stress physiological effects in young plants of Eucalyptus urophylla, helping to partially maintain the plant growth under water-limited conditions.